Sistem Manajemen Pembiayaan Sekolah dalam Peningkatan Mutu Sarana dan Prasarana SD Negeri 2 Cikalong - Andi Abdul Hanafi (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2025)
Development of Centralization and Decentralization Political Policy Changes in the socio-political atmosphere in Indonesia that emerged, as well as the economic crisis then developed into a socio-political crisis had implications for changes in various fields, including the field of education The issue of centralization and decentralization, which had previously been raised as an effort to empower the regions, has become stronger. Driven by the atmosphere of state political change, it is increasingly believed that one of the important efforts that must be made in improving the quality of education is to empower schools through MBS (School Based Management), which essentially provides authority and delegation of authority (delegation of authority) to schools to make improvements and quality continuous improvement. The approach in this research is qualitative with the type of case study research, data collection techniques through observation, interviews, documentation. The results of the research The method used in system development is the iteration method where the work of a stage can be done repeatedly and if there are errors it can be corrected immediately, the stages of the iteration method are: Survey, Analysis, Design, Creation, Implementation, Maintenance. The results of this study can be concluded that the financing available at SD Negeri 2 Cikalong School only relies on BOS funds from the government. The allocation of funds is used to meet the National Education Standards. The obstacles that exist in financing education at SD Negeri 2 Cikalong are the limited funds received from the government.